Strength parameters of masonry walls in modelling historic constructions = Parametry wytrzymałościowe murów ceglanych w modelowaniu konstrukcji zabytkowych - Gołębiewski, Michał; Lubowiecka, Izabela; Kujawa, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the determination of the basic material properties of a historic brickwork. Experimental studies were used to identify the basic material properties of bricks. The mechanical properties of the masonry, as an orthotropic homogenized material, were calculated. Then, numerical simulations using the Finite Element Method (FEM) were performed to verify the experimental outcomes. Macromodels with element sizes of 40, 20, 10 and 5 mm, and a micromodel with an element size of 5 mm were applied. The results were compared with experimental data and results available in literature.
Keywords: mury ceglane; zabytki; homogenizacja; modelowanie MES; historic brick walls; masonry structures; homogenization; FEM modeling